New entrepreneurial worlds: Can the use of role models in higher education inspire students? The case of Nigeria. Issue 4 (4th November 2019) - Adesola, Sola; den Outer, Birgit; Mueller, Sabine
Abstract : Purpose: The purpose of this paper is to determine if and how role models presented in entrepreneurship education can influence students' entrepreneurial activity given that the lack of financial and material means render most role models unattainable. Design/methodology/approach: Data were collected in three stages from an entrepreneurship workshop programme held in Lagos, Nigeria. Nigerian and European undergraduate and graduate business students worked together to develop sustainable business ideas for the European and African market. In this exploratory paper, the emphasis for analysis is on the Nigerian students. Findings: Based on the research results, the authors identified four types of role models and gained insight into how and why they could inspire students at different stages of entrepreneurship education. Research limitations/implications: This research is highly contextual with an emphasis on Europe and Africa. Given the relatively small sample of the European students in this study, this paper only presents findings from the Nigerian students. In view of time and sample size constraints, it would be useful to do a longitudinal international study to compare the approaches taken by European and African higher education institutions to develop an understanding of role models in entrepreneurship education and entrepreneurial activity. Further study is needed to explore whether role models are the way forward to address the processes of student entrepreneurial learning in the context of entrepreneurship education in Nigeria. Further work could also uncover deeper convictions, the attitudes of students with regard to race and gender, and consider implications for practice between university and industry. Practical implications: The paper contributes to the development of entrepreneurship education in the context of Nigeria's emerging economy and makes suggestions on how to stimulate entrepreneurial activity through the targeted use of role models. Social implications: In view of financial, material or societal constraints to attain role models, the result of this study can be applied in other African contexts or emerging economies to develop the understanding of the relationship between role models in the industry, higher education practices and government policy. The findings of this study show that the highest impact gained is from "real-life" exchanges between students and entrepreneurs. Originality/value: Traditional entrepreneurship education fails because the learner's process of integrating and applying behaviours of entrepreneurial examples and programmes is opaque. Research on role models suggests that where they have a positive impact is where they are perceived as self-relevant and attainable. This idea is explored in the particular context of entrepreneurship education in Nigeria in West Africa, which is characterised by highly limited and fluctuating resources despite Nigeria's relative wealth. The authors conclude with suggestions for the use of role models in entrepreneurship education, especially in the Nigerian higher education context. This paper, therefore, contributes to research on entrepreneurship role model education in emerging economies.